Avaliação de técnicas com plasma acoplado indutivamente para a determinação de constituintes inorgânicos no ciclo produtivo do frango de corte e iodo em sal de cozinha - Dionísio, Amália Geíza Gama (Universidade Federal de São Carlos, 2013)
The aim of this thesis was the development of procedures for the determination of total arsenic, selenium and chromium in chicken production-related samples and iodine in table salt using inductively coupled plasma methods. The chemical speciation of arsenic and chromium was also studied. In the first study, microwave-assisted digestion was performed using diluted nitric acid solution followed by determination using inductively coupled plasma mass spectrometry (ICP-MS) with a collision-reaction interface. In this procedure sample preparation was performed using microwave-assisted digestion with nitric acid for determinations of the elements. The second procedure was performed microwave-assisted digestion using reaction vessels pressurized with oxygen in order to regenerate nitric acid and increase the efficiency of digestion with the addition of an auxiliary reagent. Residual carbon contents determined in digests varied from 500 to 900 mg L-1. Afterwards, speciation analysis was applied for obtaining information about mobility, bioavailability and essentiality of arsenic and chromium. Thus, the speciation analysis of arsenic in chicken feed samples employing microwave-assisted extraction was investigated. The specie found was As(V) with concentration of 0.35 ± 0.06 mg kg-1. In another study, chromium speciation with sample preparation in alkaline medium was evaluated, since studies in literature showed that no interconversion occurs between Cr(VI) and Cr(III) in alkaline medium. This procedure was performed using water-soluble tertiary amines solution (CFA-C 10% v v-1) for Cr(VI) determination. The concentration of Cr(VI) in the samples ranged from 8.09 to 10.56 mg kg-1. Finally, the improvement of the sensitivity in the determination of iodine by inductively coupled plasma optical emission spectrometry (ICP OES) using the flow-blurring® multinebulizer was evaluated. The high ionization energy of iodine implies in a low ionization of this element in the argon plasma and the absorption of radiation in the VUV region by components of air, such as oxygen and water vapor, hamper this element determination by ICP OES. One alternative for improving the efficiency of nebulization and atomization of the analyte and hence the detection limits for the determination of iodine is the generation of volatile species (I2 or HI) employing oxidizing agents and reducing agents. This study was performed using sodium tetrahydroborate in alkaline medium (reducing agent) and hydrogen peroxide (oxidizing agent) in acid medium and flow-blurring® multinebulizer. The concentration of iodine in one salt sample was 131 mg kg-1.
Evaluation of methods using inductively coupled plasmas for determination of inorganic elements in chicken production-related samples and iodine in table salt
Keywords: Química; Especiação química; Cloreto de sódio; CIENCIAS EXATAS E DA TERRA::QUIMICA